Re-considering long-term athlete development on coach education: An illustration from judo - van Kooten, G. C. (International Sport Coaching Journal, 2016)
The purpose in this paper is to examine the effectiveness/usefulness of the long-term athlete development (LTAD) model, particularly in the coaching of judo. The major influences on the LTAD approach, including deliberate practice, are reviewed along with recent evidence that leads to questions about the usefulness of the LTAD model. While Judo Canada has attempted to implement this model in its program to train coaches, there remains a great deal of incongruity between the LTAD approach and the pedagogy that often characterizes judo.